A Scout of the Past: Ramsay Traquair and the Legacy of the National Art Survey of Scotland in Quebec - Murray, Irena (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Université McGill; Écossais

The Club Building / L'Édifice du Club - Drummond, Derek A. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; University Club; Université McGill

Entre globalisation et réalités locales: centres commerciaux et formes urbaines à Los Angeles, Montréal et Paris / Between Globalization and Local Realities: Shopping Centers and Urban Forms in Los Angeles, Montreal and Paris - Moretti, GianPiero (Université McGill, 2004)
Keywords: Centres commerciaux

Accessibility: A Performance Measure for Land-Use and Transportation Planning in the Montréal Metropolitan Region - Cerdá, Assumpta (Université McGill, 2009)
Keywords: Navettage

Nature's Improvement Wildlife, Conservation, and Conflict in Quebec, 1850-1914 - Ingram, Darcy (Université McGill, 2007)
Keywords: Clubs; Faune; Montreal Hunt Club; Natural History Society

Redimensioning Montreal: Circulation and Urban Form, 1846-1918 - Gilliland, Jason A. (Université McGill, 2001)
Keywords: Incendies; Port; Rues

La contestation des espaces gais au centre-ville de Montréal depuis 1950 - Guindon, Jocelyn M. (Université McGill, 2001)
Keywords: Police; Quartiers

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

Making and Using Environmental Information: An Analysis of the Development and Use of Two GIS Tools for Public Environmental Engagement - Klinsky, Sonja (Université McGill, 2004)
Keywords: West Island

Privacy in Homes of Shaamy Muslim Immigrants: A Study of Privacy Patterns in Single-Family Detached Homes and Townhouses of Middle-Class Immigrants in Montreal - Hallak, Mahmoud Essam (Université McGill, 2000)
Keywords: Musulmans; Syriens

Climate Change Adaptation and Mitigation through Urban Agriculture: A Montreal Case Study - Lebedeva, Julia (Université McGill, 2008)
Keywords: Climat

The Physical Design of Alleys: An Evaluation of Alleys in the Montreal Plateau - Wise, David (Université McGill, 2004)
Keywords: Plateau Mont-Royal; Quartiers

Making Montreal's Indoor City Accessible for People with Disabilities - Hagg, Matthew (Université McGill, 2009)
Keywords: Espace souterrain

Visual Art/Public Art and Urban Development: A Case Study of Montreal (1967-1992) - Boyce, Margaret (Université McGill, 2001)
Keywords: Centre canadien d'architecture; Jardins; Squares

Preserving Old Buildings: Adaptive Use for Residential Purposes in Montreal - Vujadinovic, Milenko (Université McGill, 2002)
Keywords: Conservation; Patrimoine

New Urbanism in Practice: An Analysis of Five Greater Montreal Area Neighbourhoods - Vannelli, Jason (Université McGill, 2009)
Keywords: Griffintown; Quartiers; Rosemont; Saint-Laurent (ville); Île-des-Soeurs

Outdoor Play Areas for Children in High-Density Housing in Montreal - Aggarwal, Monica (Université McGill, 2001)
Keywords: Enfants; Parcs; Plateau Mont-Royal; Quartiers

Stewardship as Partnership: A Comparative Study of Positive Human-Environment Relationships in East Cree and Suburban Montreal Communities - Forrest, Margaret Anne (Université McGill, 2006)
Keywords: Banlieue; Parcs; Pointe-Claire

Days and Nights: Class, Gender and Society on Notre-Dame Street in Saint-Henri, 1875-1905 - Lord, Kathleen (Université McGill, 2000)
Keywords: Quartiers; Rues; Saint-Henri

Blanche Lemco van Ginkel and H.P. Daniel van Ginkel: Urban Planning - Hodges, Margaret Emily (Université McGill, 2004)